Excited states manifold of 2, 2′-bithiophene: basis set dependence study. (17th November 2017) - Andrzejak, Marcin; Kukułka, Mercedes; Witek, Henryk A.
ABSTRACT: The 2, 2′-bithiophene energy spectra computed using a sequence of cc-pV n Z and aug-cc-pV n Z basis sets reveal surprisingly strong dependence of the excited states manifold on the quality of the basis set. The observed computational artefacts include: numerous missing states, wrong order of states and considerable shifts in the energy spectrum. The presented results suggest that the cc-pV n Z basis sets are completely unsuitable for modelling optical spectra of organic molecules and that the aug-cc-pV n Z basis sets are capable of predicting only the lowest portion of the energy spectrum. A simple and inexpensive remedy for the observed problems is suggested: an additional, molecule-centred, Rydberg basis should be rudimentarily used in quantum chemical calculations aiming at modelling optical spectra of molecules. The main conclusions of the presented study seem to be general and independent of the chemical identity of the studied system and of details of the employed computational methodology. Abstract :